2022
DOI: 10.1038/s41598-022-07213-4
|View full text |Cite
|
Sign up to set email alerts
|

Affective touch perception and longing for touch during the COVID-19 pandemic

Abstract: Interpersonal touch and affective touch play a crucial role in social interactions and have a positive influence on mental health. The social distancing regulations implemented during the COVID-19 pandemic have reduced the ability to engage in interpersonal touch. This could cause longing for touch, and it might subsequently alter the way in which affective touch is perceived. To investigate this, we conducted an online survey and included 1982 participants, which contained questions regarding the COVID-19 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 31 publications
4
32
1
Order By: Relevance
“…At the same time, E-coral is regarded as empathetic and caring and helps induce calm. This reflection echoes the findings of Meijer et al [70], which suggest that people's need for affective touch increases during the COVID-19 pandemic. We believe there is a need to further the research on tactile and haptic interaction to satisfy people's psychological and emotional needs.…”
supporting
confidence: 86%
“…At the same time, E-coral is regarded as empathetic and caring and helps induce calm. This reflection echoes the findings of Meijer et al [70], which suggest that people's need for affective touch increases during the COVID-19 pandemic. We believe there is a need to further the research on tactile and haptic interaction to satisfy people's psychological and emotional needs.…”
supporting
confidence: 86%
“…After quarantine, participants' desire to be with others decreased significantly (average difference: , slope: -0.22 ± 0.05, p < 0.001, LMM)), and their interactions with distant companions became more frequent (average difference: , slope: 0.12 ± 0.02, p < 0.001, LMM), as shown in Fig 4 . These findings suggest that when social constraints were removed, participants interacted with more people, which may have satisfied their desire to be with others, resulting in a decreased desire for further interactions with others. This result is consistent with recent EMA studies conducted during COVID-19 pandemic which showed that after months of lockdown, people felt socially isolated and expressed desire for more social interactions (Meijer et al, 2022).…”
Section: Resultssupporting
confidence: 91%
“…Finally, no significant associations were found between COVID-19 related variables and TBQ factor scores. The social distancing regulations related to the COVID-19 pandemic have reduced the ability to engage in interpersonal touch and this may alter the way in which affective touch is perceived [ 49 ]. A possible interpretation is that subjects’ pandemic-related experiences do not appear to have affected individual perceptions across the lifespan, suggesting that TBQ measures a relatively stable perception of affective touch experiences held by the individuals.…”
Section: Discussionmentioning
confidence: 99%